High cycle fatigue limit prediction of machining foreign object damaged TC17 titanium specimen based on the theory of critical distances - Kainan Lu; Yibo Shang; Chen Wang; Bin Li; Xiaosheng Zhang; Lingfeng Wang; Zhenhua Zhao; Liucheng Zhou; Wei Chen (Scientific Reports)
Abstract Aircraft engine fans and compressor blades are inevitably subject to external damage during service. It’s an important work to predict the high cycle fatigue limit of foreign object damaged blades. In this paper, machining aerofoil specimens were manufactured to simulate the foreign object damaged blade, and the high cycle fatigue limit of machining foreign object damaged TC17 titanium aerofoil specimen were tested at 3 × 107 cycles, and a high cycle fatigue limit prediction model of machining foreign object damaged TC17 titanium aerofoil specimen was built based on the theory of critical distances, and compared with the Peterson model. The prediction error is 9.56 ± 6.78% for theory of critical distance model and 59.76 ± 16.93% for Peterson model. The accuracy of fatigue limit prediction on notched samples using theory of critical distance model is much higher than that of Peterson model, and the theory of critical distances method model is more efficient to evaluate the fatigue strength of notched blade.